New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges - Jewell, Tony R. (Zootaxa, 2019)
The forest-dwelling skinks of the Oligosoma oliveri (‘marbled skink’) species-complex, from the North Island of New Zealand, have proven difficult taxonomically because all mainland populations are extinct, obscuring patterns of distribution and population interaction. Twenty-four small insular populations have survived off the north-east coast of the North Island, which are at present classified into three species. In this paper I re-assess the available phenotypic, ecological, biogeographic and phylogenetic evidence associated with these skinks. As a result, O. pachysomaticum (Robb) is raised from synonymy with O. oliveri (McCann) and more precise historical distribution limits are inferred for each member of the group. Implications for the conservation management of each species are also discussed.